Traditional Agroforestry systems for effective land management – Lessons from Indian Landscapes - Fernandaz, Cinthia; K. T. Parthiban; S. Vennila; M.Jawahar Vishnu (Indian Journal of Agroforestry, 2023)
India is basically agriculture country and known for its traditional practices. Agroforestry is one such age-old system of land management, which includes structure, function, socio-economic attributes and ecological services. Indian sub-continent with varied agroclimatic regions has representation from arid, semi-arid, humid, sub humid, humid tropics which has their own uniqueness of upholding the native tree species and agriculture crops. Agroforestry is now branded with a series of benefits to the farming community while safe guarding the environment and sustainable development. This study is an attempt to study the traditional agroforestry systems, its uniqueness and land management ecosystem services to current scenario. Maximizing the benefits to meet the rising demands for food and other ecosystem services for the well being of the societies has been the main problem for sustainable landscapes in Agriculture.